A review of the zumpti species group of the genus Harpyrhynchoides (Acariformes: Harpirhynchidae)—ectoparasites of passerines - Bochkov, Andre V; Klompen, Hans (Zootaxa, 2014)
The zumpti species group of the genus Harpyrhynchoides (Harpirhynchidae), parasites of passerines, is revised. A key to the species of this group is provided and data on host associations and geographic distribution of its constituent species are summarized. This group includes six previously recognized species: Harpyrhynchoides alaudinus Bochkov, 2000, H. brevis (Ewing, 1911) comb. nov., H. heatherae Bochkov and Galloway, 2013, H. rubeculinus (Cherny and Sixl, 1971), H. vulgaris Bochkov and Galloway, 2004, and H. zumpti (Fain, 1972). Three species from North American passerines are described as new: H. setophaga sp. nov. from Setophaga ruticilla (Parulidae), H. xanthocephalus sp. nov. from Xanthocephalus xanthocephalus (Icteridae), and H. spizella sp. nov. from Spizella passerina (Emberizidae). Additionally, H. brevis is redescribed based on samples from Coccothraustes vespertinus (type host) and Loxia curvirostra (Passeriformes: Fringillidae) from North America. Harpyrhynchoides kirgizorum Fain et al. 1999 syn. nov. is synonymized with H. zumpti.